REAKSI HIPERSENSITIVITAS ATAU ALERGI - Riwayati Riwayati (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACTHypersensitivity is the overreaction undesirable because too sensitif immune response (damaging, resulting in discomfort, and sometimes fatal) produced by the normal immune system. Reaction hipersentsitivitas have 4 types of reactions as follows: Type I: the reaction Anafilaksi, antigens or allergens are free to react with the antibody, in this case the IgE bound to mast cells or basophils cells with consequent release of histamine. This situation caused a reaction-type fast. Type II: cytotoxic reaction, the antigen bound to the target cell. In this case the IgE antibodies and IgM in the presence of complement will be provided with an antigen, which can result in the destruction of these cells. This reaction is a reaction that is rapid, and allografi reaction, ulcers Mooren is a reaction of this type. Type III: complex immune response, the antibody binds to the antigen and the complement to form immune complexes. This situation raises neurotrophichemotactic factors that could cause local inflammation or damage. Generally occur in small blood vessels.  Its presence in cornea may include herpes simplex keratitis, keratitis due to bacteria. (Stafilokok, pseudomonas) and fungi. Such reactions also occur on the Herpes simplex keratitis. Type IV: delayed type reactions, the type IV whose role is known as T lymphocytes or cellular immunity. Sensitized T lymphocytes (sensitized T lymphocytes) reacts with the antigen, and cause the release of mediators (lymphokines) which found in rejection reactions after keratoplasti, keraton- jungtivitis flikten, Herpes simplex keratitis and keratitis diskiformis. Certain diseases may be due to one or several types of hypersensitivity reactions. Kata Kunci : Hipersensitivitas, reaksi imun kompleks, imunitas seluler